A case study of urbanization impact on summer precipitation in the Greater Beijing Metropolitan Area: Urban heat island versus aerosol effects. Issue 20 (23rd October 2015) - Zhong, Shi; Qian, Yun; Zhao, Chun; Leung, Ruby; Yang, Xiu‐Qun
Abstract: Convection‐resolving ensemble simulations using the WRF‐Chem model coupled with a single‐layer Urban Canopy Model are conducted to investigate the individual and combined impacts of land use and anthropogenic pollutant emissions from urbanization on a heavy rainfall event in the Greater Beijing Metropolitan Area (GBMA) in China. The simulation with the urbanization effect included generally captures the spatial pattern and temporal variation of the rainfall event. An improvement of precipitation is found in the experiment including aerosol effect on both clouds and radiation. The expanded urban land cover and increased aerosols have an opposite effect on precipitation processes, with the latter playing a more dominant role, leading to suppressed convection and rainfall over the upstream (northwest) area, and enhanced convection and more precipitation in the downstream (southeast) region of the GBMA. In addition, the influence of aerosol indirect effect is found to overwhelm that of direct effect on precipitation in this rainfall event. Increased aerosols lead to more cloud droplets with smaller size, which favor evaporative cooling and reduce updrafts and suppress convection over the upstream (northwest) region in the early stage of the rainfall event. As the rainfall system propagates southeastward, more latent heat is released due to the freezing of larger number of smaller cloud drops that are lofted above the freezing level, which is responsible for the increased updraft strength and convective invigoration over the downstream (southeast) area. Key Points: Urbanization‐induced urban expansion and aerosol effects have an opposite effect on precipitation Aerosol suppresses (increases) rainfall in the upstream (downstream) area Aerosol indirect effect plays a dominant role in modifying rainfall pattern in Beijing